Application of the Montessori method in tercial education of a computer 3D graphics - Brožek Josef; Hamerník Dan; Veselý Petr; Svoboda Václav (IEEE (Institute of Electrical and Electronics Engineers), 2016)
The topic focuses on explain how to use Montessori method in tercial education, including examples...
Aplikace Montessori metody ve výuce počítačové grafiky v terciálním vzdělávání
Keywords: Application; the; Montessori; method; tercial; education; computer; graphics; Aplikace; Montessori; metody; výuce; počítačové; grafiky; terciálním; vzdělávání